The Influence of Self-Efficacy And Entrepreneurial Motivation On Entrepreneurial Intention Among Undergraduate Management Students At Universitas Muhammadiyah Cirebon - Fibriani, Firda; Hartati, Wiwi; Sylvani, Sylvani (Politeknik Negeri Ambon, 2025)
Introduction: This study examines the impact of self-efficacy and entrepreneurial motivation on the entrepreneurial interest of undergraduate students in the Management Study Program at the University of Muhammadiyah Cirebon. The research is grounded in the observed low levels of entrepreneurial interest among students, which are often attributed to psychological insecurity and a lack of motivational drive. The primary objective of this study is to empirically test whether self-efficacy and entrepreneurial motivation significantly predict students’ interest in entrepreneurship.Methods: This research employs a quantitative approach, utilising survey data from 92 students who have completed entrepreneurship courses.Multiple linear regression analysis was used to assess the partial and simultaneous effects of self-efficacy and entrepreneurial motivation on entrepreneurial interest.Results: The findings indicate that both self-efficacy and entrepreneurial motivation exert a positive and statistically significant influence on students’ entrepreneurial interest, both independently and in combination. These results affirm the critical role of internal psychological factors, confidence and motivation in shaping entrepreneurial intention among university students. Keywords: Self-Efficacy, Entrepreneurial Motivation, Entrepreneurial Intention